The impact of telemonitoring upon hospice referral in the community: a randomized controlled trial - Takahashi PY (Dove Medical Press, 2012)
Paul Y Takahashi,1 Gregory J Hanson,1,2 Bjorg Thorsteinsdottir,1 Holly K Van Houten,3 Nilay D Shah,3 James M Naessens,3 Jennifer L Pecina41Division of Primary Care Internal Medicine, 2Kogod Center of Aging, 3Division of Health Science Research, 4Department of Family Medicine, Mayo Clinic, Rochester, MN, USABackground: Using telemedicine for older adults with multiple comorbid conditions is a potential area for growth in health care. Given this older, ailing population, providers should discuss end-of-life care with patients.Objective: To determine the relationship between telemonitoring and hospice enrollment compared to usual care among older adults with chronic health problems.Methods: This was a secondary evaluation of a randomized controlled trial. The trial was performed at an academic medical center. Patients who were over the age of 60 and had a high risk of hospitalization and emergency department visits were recruited to the study. The primary outcome was hospice enrollment, and the secondary outcome was the mean number of days in hospice. The data were analyzed using Chi-squared tests and time-to-event analysis.Results: The average age of the cohort was 80.3 years. Nine patients (9.6%) in the telemonitoring group were enrolled in hospice care, whereas four patients (4.0%) in the usual care group were enrolled (P = 0.12). The mean number of days in hospice was 57.9 (SD ± 99.2) for the telemonitoring group, and 119.3 (SD ± 123.8) for the usual care group (P = 0.36). There was no significant difference regarding time to hospice referral.Conclusion: In this pilot analysis, there were no differences noted between groups in the number of patients that entered into hospice or the amount of time they stayed in hospice care. This was a small trial, and the power to detect a difference was 36%. It was encouraging that twice the number of patients enrolled in hospice care in the telemonitoring group compared to usual care despite the insignificant finding. Further research may determine the effect of telemonitoring upon hospice referral.Keywords: hospice, elderly, telemonitoring, palliative care